Mcph1, mutated in primary microcephaly, is also crucial for erythropoiesis - Vial, Yoann; Nardelli, Jeannette; Bonnard, Adeline A; Rousselot, Justine; Souyri, Michèle; Gressens, Pierre; Cavé, Hélène; Drunat, Séverine (EMBO reports, 2024)
Microcephaly is a common feature in inherited bone marrow failure syndromes, prompting investigations into shared pathways between neurogenesis and hematopoiesis. To understand this association, we studied the role of the microcephaly gene Mcph1 in hematological development. Our research revealed that Mcph1 -knockout mice exhibited congenital macrocytic anemia due to impaired terminal erythroid differentiation during fetal development. Anemia’s cause is a failure to complete cell division, evident from tetraploid erythroid progenitors with DNA content exceeding 4n. Gene expression profiling demonstrated activation of the p53 pathway in Mcph1 -deficient erythroid precursors, leading to overexpression of Cdkn1a/p21 , a major mediator of p53-dependent cell cycle arrest. Surprisingly, fetal brain analysis revealed hypertrophied binucleated neuroprogenitors overexpressing p21 in Mcph1 -knockout mice, indicating a shared pathophysiological mechanism underlying both erythroid and neurological defects. However, inactivating p53 in Mcph1 −/− mice failed to reverse anemia and microcephaly, suggesting that p53 activation in Mcph1 -deficient cells resulted from their proliferation defect rather than causing it. These findings shed new light on Mcph1’s function in fetal hematopoietic development, emphasizing the impact of disrupted cell division on neurogenesis and erythropoiesis — a common limiting pathway. Synopsis Mcph1, known to be required for proper neurogenesis, is also essential for erythropoiesis. Biallelic loss of Mcph1 results in a p53-independent disruption of mitosis, ultimately leading to microcephaly and severe congenital anemia. Mcph1 deficiency leads to congenital dyserythropoietic anemia in mice. Loss of Mcph1 in erythroid precursors induces acytokinetic mitosis during differentiation. Acytokinetic mitosis also occurs in neural progenitors in the absence of Mcph1. Loss of Mcph1 leads to p53 activation in both erythroid and neuroprogenitors cells. p53 inactivation fails to reverse anemia and microcephaly. Mcph1, known to be required for proper neurogenesis, is also essential for erythropoiesis. Biallelic loss of Mcph1 results in a p53-independent disruption of mitosis, ultimately leading to microcephaly and severe congenital anemia.